Plan de uso del suelo para la zona de riego del sistema Campana-Malacatos - Paredes Agurto, Sandra Beatriz (2018)
The present study proposes to elaborate a land use plan for the irrigated area of the Campana system-Malacatos, allowing to analyze the main variables that sustain this plan for which was carried the characterization and territorial diagnosis out through the socioeconomic components and biophysical. Taking as scenario the irrigation area of the "Campana system-Malacatos", located in the Canton and Province of Loja. Based on existing information plus the generation of information obtained in the field, and with the use of GIS (Geographic Information Systems) the land use plan is proposed. The first stage consists of the collection of information, the sampling that was carried out in the irrigation area, allowed to carry out the integral diagnosis and later elaborate the plan of land use. The variables analyzed were: depth, texture, pH, slope, temperature, precipitation, vegetation cover, current use, accessibility and additionally an agro-productive diagnosis was made. In the second stage, the processing of the information was carried out, which allowed the agro ecological zoning of the irrigation area of the Campana system-Malacatos, and preparation of the land use plan, through the following methodological process: identification of the potential use or preliminary zoning based on the analysis of soil potential, slopes, depth, texture and pH. Subsequently, the current use of the soil was evaluated, through the analysis of the vegetation cover and analyzed through aerial photos and verified by field trips, to then overlap with information on the potential use and obtain conflicts of land use. Next, the accessibility of the irrigation area was analyzed, when crossing it with the mapped information of conflicts the Agro ecological Zoning is defined and with its interpretation, the generation of the map of the land use plan. From this resulting zoning, three categories of land use were obtained: 1. Protection zone and agricultural production, 2. Fruit production area and 3. Area dedicated to the production of short cycle crops and with the classification of these categories of crops. Soil was formulated three projects immersed in the proposal of improvement of agricultural production.